Clinical and neurological specifics of the vertebrogenic lumbosacral radiculopathy course in the patients with RS1143627 polymorphism of the IL-1β gene - Elena A. Statinova; Natalya V. Fominova; Maria S. Kishenya (Alʹmanah Kliničeskoj Mediciny)
Rationale: Vertebrogenic lumbosacral radiculopathy (VLSRP) is a consequence of exposure to physical exertion, back injuries, and smoking. Genetic polymorphism of the cytokine IL-1β contributes to the progression of VLSRP due to its increased production in certain genetic variants.